1999
DOI: 10.1126/science.284.5417.1168
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow as a Potential Source of Hepatic Oval Cells

Abstract: Bone marrow stem cells develop into hematopoietic and mesenchymal lineages but have not been known to participate in production of hepatocytes, biliary cells, or oval cells during liver regeneration. Cross-sex or cross-strain bone marrow and whole liver transplantation were used to trace the origin of the repopulating liver cells. Transplanted rats were treated with 2-acetylaminofluorene, to block hepatocyte proliferation, and then hepatic injury, to induce oval cell proliferation. Markers for Y chromosome, di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
1,368
9
41

Year Published

2000
2000
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 2,175 publications
(1,437 citation statements)
references
References 10 publications
19
1,368
9
41
Order By: Relevance
“…Consistent with this premise, hematopoietic stem cells (HSCs) have been shown to transdifferentiate into cells of the hepatocytic lineage in both rodents and humans [16][17][18][19][20][21][22][23]. However, these findings have been challenged by studies showing that cell fusion rather than transdifferentiation of HSCs is involved in regeneration [24,25] and that bone marrow (BM) does not contribute as source of expanding oval cells [26].…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this premise, hematopoietic stem cells (HSCs) have been shown to transdifferentiate into cells of the hepatocytic lineage in both rodents and humans [16][17][18][19][20][21][22][23]. However, these findings have been challenged by studies showing that cell fusion rather than transdifferentiation of HSCs is involved in regeneration [24,25] and that bone marrow (BM) does not contribute as source of expanding oval cells [26].…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, other studies have shown that stem cells residing in one tissue can differentiate into cell types of another tissue. For example, reserve stem cells derived from bone marrow can differentiate into neurons and glia (Eglitis and Mezey, 1997;Kopen et al, 1999), restore dystrophin expression in skeletal muscle (Gussoni et al, 1999), serve as a source of hepatic oval cells (Petersen et al, 1999), provide cells for neovascularization (Asahara et al, 1999;Kalka et al, 2000), and restore cartilage, bone, and fat (Pittenger et al, 1999;Prokop, 1997;Yoo et al, 1998). Conversely, stem cells derived from neural tissues (Bjornson et al, 1999) and muscle tissues (Jackson et al, 1999) can differentiate into blood.…”
mentioning
confidence: 99%
“…not express the hematopoietic markers CD45, CD34, whereas they express variable levels of CD105 (endoglin), CD73 (ecto-5´-nucleotidase), CD44, CD90, CD29 (β1 integrin) and STRO-1 (stromal antigen 1). As depicted in Figure 7, MSC have the ability to differentiate into cells of the mesodernal lineage, like bone, fat and cartilage cells but they also have endodermic (64) and neurodermic differentiation potential (65,62). The plasticity of MSC to differentiate into cells of the hematopoietic lineage has been demonstrated in mice (66).…”
Section: Ig Gene Rearrangementmentioning
confidence: 99%